A self-reported Brazilian registry of 5q-spinal muscular atrophy: data on natural history, genetic characteristics, and multidisciplinary care - Rodrigo Holanda Mendonça; Juliane Suellen Arndt de Godoi; Edmar Zanoteli (Arquivos de Neuro-Psiquiatria)
Background Spinal muscular atrophy linked to chromosome 5q (SMA-5q) is a neurodegenerative disorder caused by mutations in the SMN1 gene.